2021
DOI: 10.1097/j.jcrs.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Macular and choroidal thickness after intracameral moxifloxacin for prevention of postcataract endophthalmitis

Abstract: Purpose: To determine any changes in macular or choroidal thickness associated with the use of intracameral moxifloxacin as postcataract endophthalmitis prophylaxis. Setting: University of Campinas, Campinas, São Paulo, Brazil. Design: Prospective, randomized, partially masked, single-site clinical trial. Methods: Phacoemulsification surgery patients in the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One study showed that preservative-free intracameral 0.5% moxifloxacin/0.1% dexamethasone ophthalmic solution, Vigadexa (Alcon, Inc.), did not lead to increased endothelial cell loss and no patient showed signs of TASS [67 ▪ ]. Other studies, including a prospective randomized trial, showed no increased safety risk, changes in macular thickness, choroidal thickness, or endothelial cell count [34,35,52,68,69,70 ▪ ]. Based on available evidence, we believe moxifloxacin is well tolerated for clinical use at approximately 0.5 mg per 0.1 ml.…”
Section: Adverse Events Associated With Intracameral Moxifloxacinmentioning
confidence: 83%
“…One study showed that preservative-free intracameral 0.5% moxifloxacin/0.1% dexamethasone ophthalmic solution, Vigadexa (Alcon, Inc.), did not lead to increased endothelial cell loss and no patient showed signs of TASS [67 ▪ ]. Other studies, including a prospective randomized trial, showed no increased safety risk, changes in macular thickness, choroidal thickness, or endothelial cell count [34,35,52,68,69,70 ▪ ]. Based on available evidence, we believe moxifloxacin is well tolerated for clinical use at approximately 0.5 mg per 0.1 ml.…”
Section: Adverse Events Associated With Intracameral Moxifloxacinmentioning
confidence: 83%
“…More recently, Ferreira et al performed a prospective randomized trial to determine whether intracameral moxifloxacin was associated with any changes in the retina and choroid. They did not find any significant differences between the moxifloxacin and control group in the thickness of the retina and choroid [ 55 ].…”
Section: Intraoperative Ocular Medicationsmentioning
confidence: 99%
“…In 2007, a major clinical study by the European Society of Cataract and Refractive Surgeons (ESCRS) (3) demonstrated the benefits of intracameral cefuroxime. Recently, three Brazilian studies have demonstrated the safety and efficacy of intracameral moxifloxacin (4)(5)(6) . Nevertheless, the adoption of such scientifically-proven strategies in clinical practice is hindered by other factors.…”
mentioning
confidence: 99%